BAKO NATIONAL PARK, BORNEO : rain forests, vegetation, and plants : including a checklist on flowering plants - Teo, Stephen P., author; Chai, Paul P. K., editor (Kuching, Sarawak : Borneo Eco, 2005)
Includes bibliographical and references